MENINGKATKAN PROSES DAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN KONTEKSTUAL MODEL CTL KELAS IV SD - M. SYAFEI (Profesi | Jurnal Ilmu Pendidikan dan Keguruan, 2014)
In general, the learning activities in school teachers still use a less conventional approach to actively involve students so that students feel tired and bored , learning is seen to be an alternative to overcome these problems is to adopt , " Application of Contextual Approach to the Study of the Distribution of Integer Math to Improve student learning Outcomes . " this study discusses the results of students' mathematics learning through contextual approach . The purpose of this study is ( 1 ) To determine the application of the contextual approach in teaching mathematics , ( 2 ) To know about improving student learning outcomes integer division using contextual approach . Methods and designs used in this study is TOD ( Classroom Action Research ) . The subject is the fourth grade students of SDN 06 Morning Kedaung Kaliangke West Jakarta 51 students consisting of 22 male students and 29 female students . The instruments used are: test , observation , student activities and angket.Dari result showed that the learning outcomes of students who take mathematics learning of mathematics by using a contextual approach has increased in comparison with conventional approaches . Student learning outcomes data were obtained before the first cycle ( before the study ) , students who gain mastery learning new 31 ( 60.78 % ) , with an average value of 6.68 . In the first cycle of students who gain mastery learning as many as 35 students ( 72.9 % ) , with an average value of 7.45 . While on the second cycle students who have gained mastery learning reaches 48 students ( 97.95 % ) with an average value of 9.06 . Study is expected to contribute to the learning approach with the application of contextual and Learning Model CTL (Contextual Teaching and Learning ) in develop instructional media to improve student learning outcomes